Therapeutic Strategies for Metastatic Triple-Negative Breast Cancers: From Negative to Positive - Dey Nandini; Aske Jennifer; De Pradip (MDPI AG, 2021)
Metastatic triple-negative breast cancer (TNBC) is a distinct and immensely complex form of breast cancer. Among all subtypes of breast cancers, TNBC has a comparatively high rate of relapse, a high rate of distant metastasis, and poor overall survival after standard chemotherapy. Chemotherapy regimens are an essential component of the management of this estrogen receptor-negative, progesterone receptor-negative, and epidermal growth factor receptor2 negative subtype of breast cancers. Chemotherapy is critical for preventing the recurrence of the disease and for achieving long-term survival. Currently, a couple of agents are approved for the management of this disease, including chemotherapy like eribulin, targeted therapy like PARP inhibitor, as well as an antibody-drug conjugate (ADC) to target TROP2. Like many other metastatic cancers, immune checkpoint inhibitors (ICIs) have also been approved for TNBC patients with PD-L1 positive tumors and high tumor mutational burden. In this review article, we discuss these newly approved and promising novel agents that may change the therapeutic landscape for advanced/metastatic TNBC patients.